Músicos de rua: luzes e sombras sobre uma prática social contemporânea no Rio de Janeiro e em Barcelona - Denise Falcão (2017)
To understand the practice of street musicians, playing in two touristic towns, Rio de Janeiro and Barcelona, in this study we have dived into the daily universe of such musicians and brought authors, such as Bauman, Delgado, Harvey, Lefebvre, Lypovetsky and Sennett, to discuss the contemporary social context of this kind of practice. It is a common scenario to find street musicians, playing through touristic towns. To understand such social dynamics, it was necessary to consider a few axes, which directed the research: the occupation of public spaces with social practices that claim a right to the city and re-signify the streets as live spaces for meetings and disputes; the aesthetic idealization of towns, which very often clashes with the diversified use of spaces by subjects, generating arguments as to how to go about the occupation and revealing the power struggle involving State, subject and society in terms of space appropriation; the development of information and communication technologies which, by challenging space-time understanding, generates transformation in social relationships in many spheres of human life, among which, work and leisure, making them fluid. To reach the proposed objective, a qualitative approach has been adopted as methodology. The ethnographic research was developed between December, 2014 and December, 2016, a year in each city, totaling 24 months of field immersion. Twenty-three semi-structured interviews were carried out and the data analysis focused on the tension involving observations in field work, political regulations, strategic planning and reports by the subjects interviewed. A critical perspective of capitalism today is present in this dissertation, based on the perception that street music, appropriated by the aesthetics of touristic towns, tries to transform an expressive part of the metropolises into consumption goods, thus imposing upon an ancient social practice, poor surviving conditions to artists. When regulated, public spaces are subject to a hygienic perspective, aiming at private occupational intentions. This measure causes tension with street appropriation by art as expression. Finally, we have come to the understanding that, despite the pressures suffered by touristic cities musicians, among other subjects, from the aesthetics of the contemporary world, this social practice resists as a possibility of expression for such musicians, through their marginal artistic makings. Slipping away through the breaches of a homogenizing system, transgressing the codes and the postulated hierarchies, street musicians keep alive a kind of social practice that sensitizes the town.